2016
DOI: 10.1007/s13337-016-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Ebolavirus evolves in human to minimize the detection by immune cells by accumulating adaptive mutations

Abstract: The current outbreak of Zaire ebolavirus (EBOV) lasted longer than the previous outbreaks and there is as yet no proven treatment or vaccine available. Understanding host immune pressure and associated EBOV immune evasion that drive the evolution of EBOV is vital for diagnosis as well as designing a highly effective vaccine. The aim of this study was to deduce adaptive selection pressure acting on each amino acid sites of EBOV responsible for the recent 2014 outbreak. Multiple statistical methods employed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…A report has even shown the use of rVSV vaccine to protect one researcher with lab exposure of EBOV [34]. Furthermore, a recent report had shown that EBOV strains undergo adaptive mutations to escape itself from detection by T and B cells of host immune system [30]. These challenges remain to increase the effectiveness of vaccines and to reduce their adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…A report has even shown the use of rVSV vaccine to protect one researcher with lab exposure of EBOV [34]. Furthermore, a recent report had shown that EBOV strains undergo adaptive mutations to escape itself from detection by T and B cells of host immune system [30]. These challenges remain to increase the effectiveness of vaccines and to reduce their adverse effects.…”
Section: Discussionmentioning
confidence: 99%